2020
DOI: 10.1186/s13018-020-02115-5
|View full text |Cite
|
Sign up to set email alerts
|

Use of the sagittal Cobb* angle to guide the rod bending in the treatment of thoracolumbar fractures: a retrospective clinical study

Abstract: Background Pedicle screw fixation is a well-established technique for thoracolumbar fracture. A large number of studies have shown that the bending angle of the connecting rod has a significant correlation with the postoperative spinal stability. However, no studies have confirmed an objective indicator to guide the bending angle of the connecting rod during the operation. Our study aims to define a sagittal Cobb* angle to guide the bending angle of the connecting rod during surgery. Methods The frontal and l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
(40 reference statements)
1
4
0
Order By: Relevance
“…Wanivenhaus et al (2019) proposed that augmented reality-assisted rod bending could reduce operation duration by 20% compared with the traditional method and achieve higher accuracy of the rod bending process. Shi et al (2020) confirmed that the Cobb angle could be used as reference to guide rod bending in thoracolumbar fractures and also reported that 4 °-8 °greater than the Cobb angle as the RC achieved the best spinal sagittal balance 2 years after the operation. Moufid et al (2019) evaluated the mismatch between rod-screw and LL of the fused segment by the concept of the mismatch analysis index (MAI), which was determined by three parameters: the angle between the screw and rod, the angle between the superior endplate and screw, and the distance between the rod and posterior wall of vertebra.…”
Section: Discussionsupporting
confidence: 56%
“…Wanivenhaus et al (2019) proposed that augmented reality-assisted rod bending could reduce operation duration by 20% compared with the traditional method and achieve higher accuracy of the rod bending process. Shi et al (2020) confirmed that the Cobb angle could be used as reference to guide rod bending in thoracolumbar fractures and also reported that 4 °-8 °greater than the Cobb angle as the RC achieved the best spinal sagittal balance 2 years after the operation. Moufid et al (2019) evaluated the mismatch between rod-screw and LL of the fused segment by the concept of the mismatch analysis index (MAI), which was determined by three parameters: the angle between the screw and rod, the angle between the superior endplate and screw, and the distance between the rod and posterior wall of vertebra.…”
Section: Discussionsupporting
confidence: 56%
“…To date, there are few studies about rod contouring in PLIF surgery. Shi et al reported that 4° to 8° greater than the cobb angle of fused segments was suggested as the optimal reference angle for rod contouring in patients with thoracolumbar fractures [10]. Their study emphasized that the accuracy of rod bending angle was important for spinal sagittal balance and prevention of adjacent disc degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…But there is still a lack of solid evidence on the correlation between rod curvature and clinical outcomes. Moreover, the appropriate degree of rod curvature is also needed to be further evaluated, although Shi et al reported that the Cobb angle could be used as a reference for rod contouring for patients with thoracolumbar fractures [10].…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study showed that there was no significant correlation between the number of fractured vertebrae and the loss of postoperative vertebral height. The sagittal Cobb angle is an important index to assess the biomechanical factors of the spine and the stability of the fracture 23–25 . Although univariate analysis showed that there was a certain correlation between preoperative sagittal Cobb angle and postoperative VHL, the sagittal Cobb angle varied greatly in different segments of the spine, and the results of multivariate logistic regression analysis showed that there was no significant correlation between sagittal Cobb angle and postoperative height loss of fractured vertebral body.…”
Section: Discussionmentioning
confidence: 99%